Estudo comparativo entre as tecnologias via úmida e via seca para a preparação de massas de porcelanatos - Melchiades, Fábio Gomes (Universidade Federal de São Carlos, 2011)
Considering the growth of the Brazilian ceramic tiles sector and its expressivity in the global setting, the present work has been developed in order to evaluate the main differences related to the preparation of bodies compositions by dry and wet route technologies and then to contribute to the viability of the porcelain tiles fabrication by dry route. The dry route can be considered the greatest technological innovation of the Brazilian ceramic tiles industry. However, despite the importance of this route to ceramic tiles fabrication, just few scientific studies were performed in order to identify its advantages and disadvantages. At the same time, in the last ten years, the porcelain tiles production showed a large growth, related to the global tendency in the sector to the diversification of production. The porcelain tiles present excellent technical properties and aesthetics effects to allow the development of ceramic products with high added value. These products have shown good penetration on market segments that are not achieved by traditional ceramic tiles. To the development of the study, it was evaluated the influence of the technology of preparation of bodies compositions on several technological parameters of relevance to the ceramic tiles production, like the medium size and the particle and granules sizes distribution, the particle and granules shapes and the degree of mixture. After that, tests were performed related to the bodies chemical compositions, the conditions of milling and granulation by dry route, to identify the necessary adjustments to feasible the porcelain tile production by this route. The results interpretation allowed to understand the importance of the technological parameters evaluated, contributing for a critical evaluation of the feasibility of producing porcelain tiles by the dry route.
Comparative study between dry and wet routes to the Porcelain tiles bodies preparation
Keywords: Porcelanato; Revestimentos cerâmicos; Materiais cerâmicos; Processos de fabricação; Formulação de materiais cerâmicos; Granulação; ENGENHARIAS